The impact of probiotics on oxidative stress and inflammatory markers in patients with diabetes: a meta-research of meta-analysis studies - Chen, Xi; Yan, Lijun; Yang, Jie; Xu, Chenlong; Yang, Lv (Frontiers in Nutrition, 2025)
ObjectiveProbiotic supplementation has gained attention for its potential to modulate inflammatory and oxidative stress biomarkers, particularly in metabolic disorders. This meta-analysis evaluates the effects of probiotics on C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), malondialdehyde (MDA), total antioxidant capacity (TAC), glutathione (GSH), and nitric oxide (NO) in patients with diabetes.MethodsA Meta-Research was conducted on 15 meta-analyses of unique 33 randomized controlled trials (RCTs) published between 2015 and 2022, involving 26 to 136 participants aged 26 to 66 years. Data were synthesized using standardized mean differences (SMD), with sensitivity analysis using a random-effect model.ResultsProbiotic supplementation significantly reduced CRP (SMD = −0.79, 95% CI: −1.19, −0.38), TNF-α (SMD = −1.35, 95% CI: −2.05, −0.66), and MDA levels (WMD: -0.82, 95% CI: −1.16, −0.47). Probiotics increased GSH (SMD = 1.00, 95% CI: 0.41, 1.59), TAC (SMD = 0.48, 95% CI: 0.27, 0.69), and NO (SMD = 0.60, 95% CI: 0.30, 0.91). Result on IL-6 was not significant (SMD = −0.29, 95% CI: −0.66, 0.09). Sensitivity analyses confirmed robustness.ConclusionProbiotics significantly improved inflammatory and oxidative stress biomarkers in patients with diabetes, with variations influenced by population and dosage. Future studies should explore novel probiotic strains and longer interventions.